86.3k views
1 vote
Given two functions f(x)=2x+4 and g(x)=−1/5x−3 , what is the function rule for (f+g)(x) ?

User PSKP
by
5.6k points

2 Answers

5 votes

Answer:

The answer is (f+g)(x)=9/5x+1

Explanation:

Given two functions f(x)=2x+4 and g(x)=−1/5x−3 , what is the function rule for (f-example-1
User Tufan
by
5.8k points
4 votes

The definition is pretty simple:


(f+g)(x) = f(x)+g(x)

So, we only have to sum the expressions:


f(x)+g(x) = 2x+4 - (1)/(5)x-3 = (9)/(5)x+1

User Danilo Bargen
by
6.0k points